Transforming Tamu into a Community-Based socioeconomic development platform - Shamsiah Syamsudin; Mohd Razalie Raffae; Norawati Ngatmin; Jaratin Lily (Human Resource Management Academic Research Society (HRMARS), 2025)
Over the past several decades, Tamu has been a canter of rural entrepreneurship and a social exchange in Sabah. However, with the modern trends of development, new challenges are presented, and the institution is becoming increasingly burdened by the barriers that undermine its effectiveness as a means of development. Among these barriers are over- dependence on a small local market, persistence in using traditional marketing tactics, limited access to digital infrastructure, and a lack of networking with community-based tourism projects. Thus, cooperatives offer a potential alternative governance structure that can comprehensively address these issues. The cooperative model would provide Tamu with a more transparent and accountable administrative framework, while also strengthening the capacity of rural businesses, promoting digital innovation, connecting the market with community-based tourism, and protecting local cultural heritage. The success of implementing this approach heavily depends on the quality of cooperative leadership, particularly in terms of strategic vision, management efficiency, and comprehensive community involvement. Therefore, cooperatives are seen as having the potential to become the main catalyst in the effort to revitalize Tamu as a sustainable and relevant rural development institution.